FORMULASI SEDIAAN SIRUP SENGKUANG Dracontomelon dao (Blanco) Merr & Rofle DAN UJI EFEKTIVITASNYA SEBAGAI ANTELMINTIK - inderiyani, Inderiyani; Puspasari, Heny; Puspita, Weni; Febrianti, Ririn (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
The bark of the sengkuang Dracontomelon dao (Blanco) Merr & Rofle stem contains secondary metabolites alkaloids, saponins, tannins, flavonoids and triterpenoids which are efficacious as anthelmintics. This study aims to formulate, physically evaluate and test the effectiveness of sengkuang stem bark ethanol extract syrup as anthelmintic against chicken roundworms (Ascaridia galli). The syrup preparation was formulated in 3 variations of extract concentrations i.e 0.2%; 0.4% and 0.6%. The syrup was physically evaluated in the form of organoleptic tests, pH, displaced volume and specific gravity. Inserting 5 chicken roundworms into each test solution i.e 0.9% NaCl (negative control), 0.5% mebendazole (positive control), sengkuang stem bark syrup 0.2%, 0.4%, and 0.6%. It was incubated at 37°C and the time and number of worm deaths were observed every 1 hour for 24 hours. The results showed the sengkuang bark ethanol extract syrup (0.2%; 0.4% and 0.6%) met the requirements in syrup preparations with brownish yellow, brownish orange and brown colors, distinctive aroma and sweet taste; pH ± 6; displaced volume ± 97-98% and specific gravity ± 1.2. All sengkuang bark ethanol extract syrup formulations had the ability to kill 100% of worms with LT50 values ​​of 11.40 hours; 10.33 hours and 6.87 hours.